Answer: [tex]by \: pythagoras \: theorem \\ = {a}^{2} + {b}^{2} = {c}^{2} \\ {40}^{2} + {b}^{2} = {50}^{2} \\ 1600 + {b}^{2} = 2500 \\ {b}^{2} = 2500 – 1600 \\ {b}^{2} = 900 \\ b = \sqrt{900} \\ b = 30[/tex] Step-by-step explanation: Pls Mark this answer as the brainliest Reply
Answer:
[tex]by \: pythagoras \: theorem \\ = {a}^{2} + {b}^{2} = {c}^{2} \\ {40}^{2} + {b}^{2} = {50}^{2} \\ 1600 + {b}^{2} = 2500 \\ {b}^{2} = 2500 – 1600 \\ {b}^{2} = 900 \\ b = \sqrt{900} \\ b = 30[/tex]
Step-by-step explanation:
Pls Mark this answer as the brainliest